Note-Taking Skills of Middle School Students With and Without Learning Disabilities - Boyle, Joseph R. (Journal of learning disabilities, 2010)
For middle school students with learning disabilities (LD), one major component of learning in content area classes, such as science, involves listening to lectures and recording notes. Lecture learning and note-taking are critical skills for students to succeed in these classes. Despite the importance of note-taking skills, no research has been reported on the problems that school-age students with LD encounter when recording notes during science lectures. Using a sample size of 90 middle school students, the performance of students with LD was compared to students with no learning disabilities (NLD). Results found that students with LD performed significantly worse than students with NLD in terms of the type and amount of notes recorded and test performance.